Enzymatic virgin coconut oil effect on urea and creatinine levels of hypercholesterolemia-diabetics induced Wistar male rats - Dewi, Niluh Puspita; Alaydrus, Syafika; Nadila, Nadila; Magfirah, Magfirah; Tandi, Joni; Anggi, Viani; Astria, Nani (Pharmaciana, 2024)
Coconut (Cocos nucifera) is an Indonesian commodity that has high economic value tall. Virgin Coconut Oil (VCO) is one of the processed coconut products whose selling value is very high, because The composition of VCO consists of medium-chain fatty acids that can maintain a healthy body and prevent various diseases. The process of making VCO used in This research is an enzymatic method using pineapple weevil as a bromelain enzyme. This study aims to determine the effect of enzymatic administration of VCO and an enzymatic dose of VCO which is effective in reducing urea and creatinine levels in hypercholesterolemic-diabetic male white rats (Rattus norvegicus). This study was an experimental laboratory with a modified pretest and posttest randomized controlled group design using 30 test animals which were divided into 6 treatment groups. Each group consisted of 5 test animals, namely normal control, negative control, and positive control, with doses of 0.2, 0.4, and 0.8 mL/kg BW. The data obtained were analyzed using a One Way Anova and non- parametric statistical test by Kruskal Wallis. test and followed by a further Mann Whitney test to determine differences between treatments. The results showed that enzymatic VCO at a dose of 0.8 mL/kg BW was an effective dose in reducing urea and creatinine levels with an average decrease of 17.40 mg/dL and 0.36 mg/dL. The novelty in this study showed that the enzymatic VCO had an effect on reducing urea and creatinine levels in diabetic hypercholesterolemic male white rats.